The “state of the art” of intraoperative neurophysiological monitoring: An Italian neurosurgical survey - Riccardo Antonio Ricciuti; Fabrizio Mancini; Giusy Guzzi; Daniele Marruzzo; Alessandro Dario; Alessandro Della Puppa; Alessandro Ricci; Andrea Barbanera; Andrea Talacchi; Andreas Schwarz; Antonino Germanò; Antonino Raco; et al. (Brain and Spine)
Introduction: Intraoperative Neurophysiological Monitoring (IOM) is widely used in neurosurgery but specific guidelines are lacking. Therefore, we can assume differences in IOM application between Neurosurgical centers. Research question: The section of Functional Neurosurgery of the Italian Society of Neurosurgery realized a survey aiming to obtain general data on the current practice of IOM in Italy. Materials and methods: A 22-item questionnaire was designed focusing on: volume procedures, indications, awake surgery, experience, organization and equipe. The questionnaire has been sent to Italian Neurosurgery centers. Results: A total of 54 centers completed the survey. The annual volume of surgeries range from 300 to 2000, and IOM is used in 10–20% of the procedures. In 46% of the cases is a neurologist or a neurophysiologist who performs IOM. For supra-tentorial pathology, almost all perform MEPs (94%) SSEPs (89%), direct cortical stimulation (85%). All centers perform IOM in spinal surgery and 95% in posterior fossa surgery. Among the 50% that perform peripheral nerve surgery, all use IOM. Awake surgery is performed by 70% of centers. The neurosurgeon is the only responsible for IOM in 35% of centers. In 83% of cases IOM implementation is adequate to the request. Discussion and conclusions: The Italian Neurosurgical centers perform IOM with high level of specialization, but differences exist in organization, techniques, and expertise. Our survey provides a snapshot of the state of the art in Italy and it could be a starting point to implement a consensus on the practice of IOM.